For her consideration - Spalding, Amy (Kensington Publishing Corp., 2023)
"When an aspiring L.A. scriptwriter falls head-over-heels for a bossy and beautiful movie star after a devastating break-up, the two take a risk on love and cast themselves as the leading ladies of their own star-struck romance in this sweet and spirited love story from critically-acclaimed writer Amy Spalding in her adult debut"--